Bracketed morality in adolescent football players: A tale of two contexts. (March 2021) - Kavussanu, Maria; Ring, Christopher
Abstract: Background: The concept of bracketed morality has received some empirical support in several sport studies. In this research, we examined bracketed morality in adolescent football players. Specifically, we investigated: (a) whether moral behaviour differs between two contexts - sport and school - and whether these differences are moderated by age and sex; and (b) whether context differences in moral behaviour are explained by corresponding context differences in peer motivational climate, moral disengagement, and empathy. Design: We conducted two studies using a cross-sectional design. Method: In both studies, adolescent football players completed measures of prosocial and antisocial behaviour toward their teammates and opponents in sport and toward their classmates in school. Participants also completed measures of peer motivational climate (Study 1) and moral disengagement and empathy (Study 2) in the two contexts. Results: Across the two studies and all age groups, prosocial teammate behaviour was more frequent in sport than school; the opposite pattern was revealed for prosocial opponent behaviour. Antisocial teammate behaviour was less frequent in sport than school in younger athletes, but there was no (overall) context difference in older athletes. In Study 2, in girls, antisocial opponent behaviour was more frequent in sport than school across all age groups. In boys, this behaviour was less frequent in sport than school in early adolescence, but this pattern was reversed in middle and late adolescence. Context differences in task peer climate accounted for context differences in the two prosocial behaviours, while context differences in moral disengagement accounted for context differences in the two antisocial behaviours. Conclusions: Our findings extend the concept of bracketed morality to moral behaviour in sport and school in adolescents and suggest that by intervening on task peer climate and moral disengagement we could reduce the gap in prosocial and antisocial behaviours between the two contexts. Highlights: Prosocial behaviour was more frequent toward teammates and less frequent toward opponents in sport than toward classmates in school. Participants reported lower antisocial behaviour toward teammates in sport than toward classmates in school. Age and sex moderated the sport-school differences in antisocial opponent behaviour. Task peer climate partially mediated context differences in prosocial behaviour. Moral disengagement partially mediated context differences in antisocial behaviour.